Synchronous bacterial barrier and exudate absorption: A novel dual-function dressing strategy for pin-site infection prevention - Bing Liang; Sha Zhou; Linyuan Xue; Qizun Wang; Qianqian Li; Zihan Zheng; Xinyue Ma; Jiyixuan Li; Li Sun; Kunyue Xing; Xiaobo Wen; Xiaolin Wu; et al. (Materials Today Bio)
Open pin-site wounds, with infection rates of 11 %–100 %, pose significant clinical challenges, affecting millions globally and often leading to life-threatening complications. Current dressings fail to simultaneously block bacterial invasion and manage internal wound infection, necessitating innovative solutions. This study introduces PINSHIELD, a dual-functional dressing that externally seals wounds while efficiently managing exudate to mitigate pin-site infections (PSI). The external shell provides a physical barrier, while the embedded zinc alginate-polyurethane (ZAPU) layer combines active antibacterial properties with passive bacterial adhesion. The optimized ZAPU structure absorbs exudate and regulates the wound microenvironment, inhibiting bacterial proliferation and limiting infection spread. In vitro studies demonstrated that PINSHIELD inhibited S. aureus and E. coli by 90 %, with a bacterial blocking efficiency exceeding 95 %, significantly outperforming traditional gauze. In vivo results showed reduced inflammation, bacterial loads, and Staphylococcus abundance, while enhancing microbial diversity and enriching health-associated bacteria. Transcriptomic and metabolomic analyses revealed that PINSHIELD downregulated key S. aureus virulence genes (cna, SSL family, aur) and disrupted essential metabolic pathways (e.g., fatty acid biosynthesis, aminoacyl-tRNA synthesis), impairing bacterial adhesion, immune evasion, and biofilm formation. By synchronizing bacterial barrier formation with exudate management, PINSHIELD addresses the complex pathological needs of PSI, enhancing therapeutic efficacy and wound healing. This innovative design provides a versatile platform for infection control and personalized wound care, with broad implications for treating open wounds in orthopedic and other invasive device scenarios.